A novel method for left anterior coronary artery flow velocity assessment by transthoracic echocardiography at the peak of a supine bicycle test - Zagatina, Angela; Zhuravskaya, Nadezhda; Egom, Emmanuel; Kovacova, Gabriela; Kruzliak, Peter (Acta radiologica (Stockholm. 1987), 2016)
BACKGROUND: Assessment of coronary flow is only performed during pharmacological tests. Supine bicycle tests permit the visualization of coronary flow assessments during exercise. PURPOSE: To assess the parameters of coronary flow in the left anterior descending artery (LAD) during exercise, which could be a sign of significant LAD narrowing. MATERIAL AND METHODS: A total of 253 patients were enrolled: Group 1, 186 non-selective participants before undergoing a coronary angiography; and Group 2, 67 controls without coronary artery disease (CAD). All the patients performed a supine bicycle echocardiography test. Coronary flow velocities and coronary flow velocity reserve (CFVR) were measured at the mid-segment of the LAD during exercise. Patients in Group 1 underwent a coronary angiography. RESULTS: In comparison with participants without significant LAD stenosis, patients with LAD lesions had a lower ΔV (16 ± 21 vs. 27 ± 20 cm/s, P < 0.04) and a lower CFVR (1.5 ± 0.8 vs. 2.0 ± 0.6, P < 0.004). In comparison with patients without significant proximal LAD stenosis, the patients with proximal LAD lesions had a lower flow velocity at the peak of exercise (49 ± 32 vs. 61 ± 19 cm/s, P < 0.02), a lower ΔV (13 ± 19 vs. 26 ± 22 cm/s, P < 0.004), and a lower CFVR (1.4 ± 0.6 vs. 1.9 ± 0.7, P < 0.0001). In comparison with the control group, the patients with LAD stenosis had a lower flow velocity at the peak of exercise, a lower ΔV, and a lower CFVR. CONCLUSION: Non-invasive CFVR measurement in the LAD could provide valuable additional information to a conventional echocardiography exercise test. In routine clinical practice, CFVR is sufficient for a diagnosis of severe stenosis.
Keywords: cyklistika; Blood Flow Velocity; Coronary Angiography; studie případů a kontrol; Humans; Echocardiography, Doppler, Pulsed; lidé středního věku; Middle Aged; zátěžová echokardiografie; rychlost toku krve; pulzní dopplerovská echokardiografie; mužské pohlaví; koronární nemoc; koronární cirkulace; Bicycling; Coronary Circulation; Coronary Disease; ženské pohlaví; Echocardiography, Stress; Exercise Test; zátěžový test; lidé; Case-Control Studies; Male; koronární angiografie; Female